Послойная эквивалентность гладких функций на поверхностях с изолированными критическими точками - Лычак, Д.П. (Інститут математики НАН України, 2009)
This paper studies smooth functions with isolated critical points. They are considered to within fiber equivalence. The fd-graph, which specifies the f-atom, is constructed. The necessary and sufficient condition for fiber equivalence of smooth functions is formulated.